2003
DOI: 10.1084/jem.20021842
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor Nur77 Is Involved in Caspase-independent Macrophage Cell Death

Abstract: Activation-induced cell death in macrophages has been observed, but the mechanism remains largely unknown. Activation-induced cell death in macrophages can be independent from caspases, and the death of activated macrophages can even be triggered by the pan-caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp-fluoromethyl ketone (zVAD). Here, we show that this type of macrophage death can occur in the septic mouse model and that toll-like receptor (TLR)-2 or TLR4 signaling is required in this process. We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 56 publications
7
67
0
Order By: Relevance
“…On the contrary, zVAD enhance the cell death slightly (Figure1B). Consistent with earlier reports [22], we also found that zVAD treatment could prime macrophages for subsequent cell death induced by LPS ( Figure 1B). …”
Section: Lps Induces Cell Death In Primed Macrophagessupporting
confidence: 93%
See 4 more Smart Citations
“…On the contrary, zVAD enhance the cell death slightly (Figure1B). Consistent with earlier reports [22], we also found that zVAD treatment could prime macrophages for subsequent cell death induced by LPS ( Figure 1B). …”
Section: Lps Induces Cell Death In Primed Macrophagessupporting
confidence: 93%
“…For example, LPS was reported to cause cell death of conA or IFN-γ primed macrophages and to enhance cell death induced by the Yersinia baccillus [17,20,21]. Intriguingly, it was found that zVAD and boc-D, pan-caspase inhibitors that inhibit apoptosis in many different cells, not only had no inhibitory effect on LPS-induced apoptosis in INF-γ primed macrophages but also by themselves induced susceptibility to LPS-induced cell death in macrophages [22]. As zVAD treatment can prime macrophages for LPSinduced cell death, a previous study by Kim et al utilized this model system to investigate the underlying molecular mechanisms [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations